Teachers’ Perception, Plan, and Implementation of Portfolio Assessment in Students’ Writing Assessment - Virgin, Junnilalita Aisya; Anggani Linggar Bharati, Dwi (Universitas Negeri Semarang, 2020)
This study aims to investigate how teachers perceive, plan and implement portfolio assessment in students’ writing assessment. a acse study as a part of qualitative reserch design is employed in this study. The study involved an English teacher of SMP N 8 Semarang (#T2) and an English teacher of SMA N 2 Semarang (#T1). The data were gathered through questionnaire, interview, observation and documents analysis. From the results of analysis, the study revealed that both teachers had positive perception of portfolio assessment in students’ writing assessment. That was indicated from their agreement and positive thoughts on portfolio development and implementation, its effectiveness as an educational tool and its influence on the instructional practices, teacher and students’ roles and responsibilities during the portfolio development. Unfortunately, their portfolio knowledge was insufficient. The two partcipants lesson plans analysis showed that teachers have unplanned portfolio development. That was seen from their lesson plans which portfolio steps and rubric could not be found. Teachers portfolio development and implementation run less succesfully. That was because teachers lack of preparation of the portfolio, the absence of students’ self-assessment or reflection and there was no clear rubric of assessment that teachers prepared. Time management, storage and portfolio rubric became the main problems that teachers faced during their journey in developing portfolio. Furthermore, teachers’ positive perception was not aligned with their portfolio plan. Misalignment also found between teachers’ good perception with their classroom practices. That was because teachers missed several essential elements of portfolio. One of the factor is because teachers have insufficient portfolio knowledge. Some training and workshops as well as individual professional development were needed for the teachers in order to improve their professional development.